Analysis of Time and Cost Efficiency through the Application of Design Review on the Bridge Rehabilitation Project in Bantuas Village, Samarinda City - Amir Mudrajad; Risma Marleno; Jaka Purnama (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2026)
The application of review design in construction projects serves as an effective strategy to enhance implementation efficiency. This study aims to analyze time and cost efficiency resulting from the application of review design in the Bantuas Bridge rehabilitation project in Samarinda City. The research employs a comparative analysis between the initial design and the revised design, evaluating construction methods, equipment productivity, activity duration, and cost requirements. Data were collected from planning documents, cost estimates, technical reports, and field observations. The results indicate that the review design reduced project duration from 150 to 140 days, achieving a time efficiency of 6.67%. Additionally, the total project cost decreased from Rp3,000,487,000 to Rp2,860,487,000, resulting in a cost saving of 4.67%. These efficiencies were achieved through the adoption of precast minipile foundations and modular structural components such as steel decks. Therefore, the review design is proven to be an effective strategy for improving construction efficiency in terms of time and cost.